Condemned to repetition? : the rise, fall, and reprise of Soviet-Russian military interventionism, 1973-1996 - Bennett, Andrew, 1960- (BCSIA studies in international security., 1999)
"Why did the Soviet Union use less force to preserve the Soviet empire from 1989 to 1991 than it had used in distant and impoverished Angola in 1975? This book fills a key gap in international relations theories by examining how actors' preferences and causal conceptions change as they learn from their experiences."--Jacket